NEW BLUE GIANTS BETWEEN GALACTIC COORDINATES L345 TO L35 - IRIARTE ERRO, B; CHAVIRA, E (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1956)
We present a new list of 176 stars in a region near the galactic equator between l=345° and 35° that have been classified tentatively as supergiants. The data were obtained on objective prism plates, taken with the Tonantzintla Schmidt camera.
BOL OBS TONAN TACUB
Keywords: NEW, BLUE GIANTS, GALACTIC; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS